ChemInform Abstract: The Development of Highly Active Acyclic Chiral Hydrazides for Asymmetric Iminium Ion Organocatalysis. Issue 14 (8th April 2014) - Gould, Eoin; Lebl, Tomas; Slawin, Alexandra M. Z.; Reid, Mark; Davies, Tony; Smith, Andrew D.
Abstract Double asymmetric induction is employed as a tool to optimize pyrazolidinone derived organocatalysts for the asymmetric iminium ion catalyzed Diels—Alder reaction.